SISTEM BUKA KUNCI OTOMATIS RFID BERDASARKAN SISTEM INFORMASI PENJADWALAN GENETIKA - Indra Dwi Cahya Septiandi; Missi Hikmatyar; Ega Nugraha (Jurnal Informatika Teknologi dan Sains, 2022)
Facilities at Universitas Perjuangan every period there is always repair or replacement. This happened because of the lack of control over access to classrooms at Universitas Perjuangan. This RFID automatic unlocking system based on genetic scheduling aims to manage classrooms in order to maintain existing facilities, so that unauthorized persons cannot use the room. The author completed this through several stages including data collection by observation and interviews, data analysis, design of tools and information systems, implementation of tools and information systems, trials, and integration. Based on the test results, it can be concluded that the implementation of the automatic unlock system based on genetic scheduling can work according to the designed working principle. This is shown in all circuits when working, the microcontroller can send the UID that is faced and also the information system can respond and adjust to the schedule database that is active every time.